Influencia de dos dosis de abonos orgánicos sobre el comportamiento agronómico y productivo en la asociación maíz (Zea mays) fréjol (Phaseolus vulgaris L). - Esmeralda Carriel, Adelaida Lisseth (2017)
The association of crops is becoming increasingly important and becomes attractive to farmers as it gives them the opportunity to associate two or more crops in a single land taking advantage of the largest possible space, organic fertilizers is a more ecological and tentative strategy, since Helps to increase the development and production of crops. For this reason, the objective of this research was to determine the influence of two doses of organic fertilizers on the agronomic and productive behavior in the corn-fréjol association. The trial was carried out during the period of August-December 2016, Association of Farmers "April 26" belonging to the "Guarumal de Environnement" Campus, Canton Mocache of the Province of Los Ríos, for the establishment of the trial were distributed lowered an experimental design of complete blocks at random with factorial arrangement 3 x 2 + 3 in three repetitions to have the smallest possible error. The experimental results were subjected to the analysis of variance and the Tukey test at 95% probability. The treatments studied were: Dung Te, Biol, Bayfolan Aktivator. To test the effect of organic fertilizers on the maize - bean association using the maize hybrid Somma and the bean variety (Pata de Paloma) with excellent productive characteristics, thus having eighty - five plants per plot, forty - five maize and Forty bean, applying 6 treatments, three replications were performed to have the smallest error possible the total treatments in the investigation were 27. As the main results it was observed that using Bayfolan Aktivator at 35 days the maize crop was obtained the highest plant height with 82.3 cm and when the Biol was applied at 50 days the highest height was obtained with 1.7 M, days at flowering and ear length did not show differences to the application of fertilizers, when the Biol was obtained the highest height of insertion of ears per plant with 78.3 cm, Bayfolan Aktivator presented the highest Length of ears per plant with 18.2 cm, the largest diameter of ear with 5.2 cm, the best weight of 100 seeds with 36.1 g. And the highest yield with 5798.2 kg / ha. In the bean crop the application of Biol at doses of 150 l / ha obtained the highest plant height with 16.4 cm at 20 days, and when Bayfolan Aktivator was applied at doses of 150 l / ha at 35 days, The best height of plants with 28.1 cm and Bayfolan Aktivator at doses of 50 l / ha presented the highest plant height at 50 days with 54.8 cm. The days at flowering the number of pods per plant and the number of grains per pod were maintained at equal averages each of these variables respectively did not show differences to the application of the different fertilizers and their doses when applied the Bayfolan Aktivator se Obtained the highest number of grains per plant with 125.7 g. And the application of Biol in doses of 150 l / ha obtained the highest length of pods with 9.4 cm. The control maize - bean (farmer technology) obtained the highest weight of 100 seeds with 25.3 g. But the other treatments were maintained with similar weights, the best performance was presented in the application of Bayfolan Aktivator of 2 l / ha which generated a weight of 656.9 kg / ha. When Bayfolan Aktivator was applied the highest profit was achieved with 1882.93 reflecting a benefit / cost ratio of $ 1.41. KEYWORDS: Crop association, maize, beans, agronomic behavior, organic fertilizers.